2000
DOI: 10.1007/s004679900254
|View full text |Cite
|
Sign up to set email alerts
|

Gastroduodenal lesions and Helicobacter pylori in children with end-stage renal disease

Abstract: Thirty-seven children with end-stage renal disease were evaluated for gastroduodenal lesions by upper gastrointestinal endoscopy between January 1993 and January 1998. The mean (+/-SD) age of the patients was 14.3+/-2.4 years (range 9-17 years). Endoscopic examination was abnormal in 17 patients (46%). The lesions were antral gastritis plus bulbitis (n=6), nodular bulbitis (n=4), antral gastritis (n=4), and duodenal ulcer (n=3). Fifteen patients had symptoms related to gastroduodenal disease, whereas 22 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
8
3
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 32 publications
5
8
3
2
Order By: Relevance
“…The gastric mucosa of approximately 50% of the world's population is infected with H. pylori, and the infection levels exceed 70% in some developing areas (14,15). Helicobacter pylori infection plays a crucial role in the development of gastrointestinal diseases, such as peptic ulcer, gastric hyperplastic polyps, gastric adenoma, gastric cancer, and gastric mucosa associated-lymphoid tissue lymphoma, both in individuals with normal renal function and in chronic renal failure patients receiving hemodialysis and CAPD (Tables 1 and 2) (4-9, 16,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]34,[36][37][38][39][40][41][42][43][44][45][47][48][49][50][51][52][53][54][55][56][57][58][59][60].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The gastric mucosa of approximately 50% of the world's population is infected with H. pylori, and the infection levels exceed 70% in some developing areas (14,15). Helicobacter pylori infection plays a crucial role in the development of gastrointestinal diseases, such as peptic ulcer, gastric hyperplastic polyps, gastric adenoma, gastric cancer, and gastric mucosa associated-lymphoid tissue lymphoma, both in individuals with normal renal function and in chronic renal failure patients receiving hemodialysis and CAPD (Tables 1 and 2) (4-9, 16,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]34,[36][37][38][39][40][41][42][43][44][45][47][48][49][50][51][52][53][54][55][56][57][58][59][60].…”
mentioning
confidence: 99%
“…[4][5][6][7][8][9]16,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]34,[36][37][38][39][40][41][42][43][44][45][48][49][50][51][52][53][54][55][56][57][58][59][60], the prevalence of H. pylori infection in patients receiving chronic hemodialysis and CAPD are 43.9% ([95% CI: 42.2-45.6%], 1 435/3 272) and 34.8% ([29.6-40.2%], 113/325), respectively, which is significantly lower than in individuals with normal renal function both with and without gastrointestinal symptoms (49.8% [48.0-51.7%], 1476/2961, P < 0.001).There is variation in H. pylori infection rates among different countries. It may, therefore, be better to evaluate the infection rate in various countries.…”
mentioning
confidence: 99%
“…Sıkça gözlenen kusma ve dispeptik yakınmalar iştah kaybına, yetersiz kalori alımına sebep olmakta ve çocuklarda büyüme ve gelişmeyi olumsuz etkilemektedir (1,2).…”
Section: Gi Riflunclassified
“…Çoğu asemptomatik olsa da bu inflamasyon gastrit, gastro-duodenal ülser ve hatta gastrik kansere neden olabilmektedir. Üremik hastalarda, çeşitli ve çok sayıda ilaç kullanma zorunluluğu, mide boşalma zamanında uzama ve serum gastrin düzeyinde artış gibi nedenlerle dispeptik yakınmalar sık görülmekte, HP enfeksiyonunun da eklenmesi ile bu yakınmaların sıklığı artmaktadır (2)(3)(4)(5)(6)(7)(8).…”
Section: Gi Riflunclassified
“…The authors concluded that renal transplantation is safe, even in patients with a history of peptic ulcer disease (490). Recognition of the role of Heliobacter pylori and its treatment have also helped reduce the morbidity associated with peptic ulcer disease (491)(492)(493)(494). However, routine screening for Heliobacter pylori is generally not recommended (495-499).…”
Section: The Evaluation Of Renal Transplant Candidates: Clinical Pracmentioning
confidence: 99%